Modeling of Nitrogen Dynamics in an Austrian Alpine Forest Ecosystem on Calcareous Soils: A Scenario-Based Risk Assessment under Changing Environmental Conditions - Friedl Herman; Stefan Smidt; Klaus Butterbach-Bahl; Michael Englisch; Ernst Gebetsroither; Robert Jandl; Klaus Katzensteiner; Manfred Lexer; Friederike Strebl; Sophie Zechmeister-Boltenstern (The Scientific World Journal)
We modeled the behavior of an Austrian alpine forest ecosystem on calcareous soils under changing climate and atmospheric nitrogen deposition scenarios. The change of nitrate leaching, emission rates of nitrogen compounds, and forest productivity were calculated using four process-oriented models for the periods 1998–2002 and 2048–2052. Each model reflects with high detail a segment of the ecosystem: PnET-N-DNDC (photosynthesis-evapotranspiration-nitrification-denitrification-decomposition; shortterm nitrogen cycling), BROOK90 (water balance for small and homogenous forest watersheds), HYDRUS (water flux in complex and heterogenous soils), and PICUS v1.3 (forest productivity). The nitrogen balance model (NBM) combines the individual results into a comprehensive picture and extends the specific values beyond the limits of the individual models. The evaluation of the findings was outlined with TRACE, a model enabling a long-term prognosis of nitrogen cycling in annual time steps.